Cyberwar and revolution : digital subterfuge in global capitalism - Dyer-Witheford, Nick, 1951-; Matviyenko, Svitlana, 1976- (University of Minnesota Press, 2019)
Global surveillance, computational propaganda, online espionage, virtual recruiting, massive data breaches, hacked nuclear centrifuges and power grids--concerns about cyberwar have been mounting, rising to a fever pitch after the alleged Russian hacking of the U.S. presidential election and the Cambridge Analytica scandal. Although cyberwar is widely discussed, few accounts undertake a deep, critical view of its roots and consequences. Analyzing the new militarization of the internet, Cyberwar and Revolution argues that digital warfare is not a bug in the logic of global capitalism but rather a feature of its chaotic, disorderly unconscious. Urgently confronting the concept of cyberwar through the lens of both Marxist critical theory and psychoanalysis, Nick Dyer-Witheford and Svitlana Matviyenko provide a wide-ranging examination of the class conflicts and geopolitical dynamics propelling war across digital networks. Investigating the subjectivities that cyberwar mobilizes, exploits, and bewilders, and revealing how it permeates the fabric of everyday life and implicates us all in its design, this book also highlights the critical importance of the emergent resistance to this digital militarism--hacktivism, digital worker dissent, and off-the-grid activism--for effecting different, better futures.